The Periodical inspection in training young players in "UKS Football School" Chelmno - Stępniak, Robert; Pabianek, Łukasz; Ostrowska, Daria (Journal of Education, Health and Sport, 2017)
The aim of the study was to assess the impact of the training process at the level of motor skills among junior footballers and footballers team, "UKS School Football" Chelmno. Tests were conducted in the seven-month period of time. Analysis of selected samples also had the task to confirm the validity of conducting such activities in the current and periodic inspections in the process of training players. RAST test was conducted, BEEP test and control gear for a distance of 30m from the measurement of lap 5 and 10m. Both age groups improved their scores in both tests, speed events, as well as endurance. The average score on the run for 30 m among footballers was a first attempt 5.10 s, and in the second it was already 5.04 seconds. Juniors in the first study received a mean score of 4.41 s, and in the second 4.36 seconds. Also improved RAST test, where the average power in one section in the older group was 7.3 W / kg in the first trial and 8.1 W / kg in the second sample. Younger achieved the same result in both trials and was 5 W / kg. BEEP test also brought the expected improvement in results. Research and analysis verified the positive quality of training young footballers of the Club of Chelmno at the same time confirms the use of the described research tools in the process of checking in sports.